The Impact of Sales Promotion Tools on Consumer Buying Behavior towards Refrigerator in Kathmandu Valley - Chand, Ekata (Nepalese Journal of Business, 2025)
This study examines the impact of sales promotion tools on consumer buying behavior towards refrigerator in Kathmandu valley. Consumer buying behaviour is selected as the dependent variable. Similarly, coupon, free sample, product warranty, price discount, festive offer, buy-one-get-one free and are selected as the independent variables. This study is based on primary data with 129 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different promotional tools influencing consumer buying behavior towards refrigerator in Kathmandu valley. The study showed that coupon has a positive impact on consumer buying behaviour. It means that increase in implementation of coupon leads to increase in consumer buying behaviour. Similarly, free sample has a positive impact on consumer buying behaviour. It indicates that increase in free sample leads to increase in consumer buying behaviour. Moreover, product warranty has a positive impact on consumer buying behaviour. It means that increase in product warranty leads to increase in consumer buying behaviour. Likewise, price discount has a positive impact on consumer buying behaviour. It shows that increase in price discount leads to increase in consumer buying behaviour. Similarly, price discount has positive impact on consumer buying behaviour. It shows that higher the price discount, higher would be the consumer buying behaviour. Likewise festive offer has a positive impact on consumer buying behaviour. It indicates that increase in festive offer leads to increase in consumer buying behaviour Further, buy-one-get-one free has a positive impact on consumer buying behaviour. It shows that higher the buy-one-get-one free tool, higher would be the consumer buying behaviour.